HUBUNGAN KONDISI LINGKUNGAN RUMAH DAN KEBIASAAN MEROKOK ANGGOTA KELUARGA DENGAN KEJADIAN ISPA PADA ANAK USIA 1-10 TAHUN DI WILAYAH KERJA PUSKESMAS BUNTUL KEMUMU - Rahmi; Nurlaely HS (Akper Kesdam I/Bukit Barisan Padang, 2026)
ABSTRACT Acute Respiratory Tract Infection (ARI) is an upper or lower respiratory tract disease that is usually contagious and can cause various diseases, ranging from asymptomatic or mild infections to severe and fatal diseases, depending on the causative pathogen, environment, and host. This study aims to determine the Relationship between Home Environmental Conditions and Family Members' Smoking Habits with the Incidence of ARI in Children Aged 1-10 in the Buntul Kemumu Community Health Center Working Area. The type of research is descriptive correlational using a cross-sectional approach method. The number of samples in this study was 91 respondents. The sampling technique used simple random sampling. The results of the study showed that 51 respondents (56.0%) had unqualified home environmental conditions, 69 respondents (75.8%) had smoking habits in the home, and 67 respondents (73.6%) had medically diagnosed acute respiratory infections. The results of the Chi-Square statistical test obtained p values ​​(0.000) and (0.001). These results conclude that there is a relationship between the condition of the home environment and the smoking habits of family members with the incidence of ARI in children aged 1-10 years in the Buntul Kemumu Community Health Center work area. Keywords : Home Environmental Conditions, Smoking Habits, Incidence of ARI